Association of Low Luminance Questionnaire With Objective Functional Measures in Early and Intermediate Age-Related Macular Degeneration - Thompson, Atalie C.; Luhmann, Ulrich F. O.; Stinnett, Sandra S.; Vajzovic, Lejla; Horne, Anupama; Toth, Cynthia A.; Cousins, Scott W.; Lad, Eleonora M. (Investigative ophthalmology & visual science, 2018)
To determine whether Low Luminance Questionnaire (LLQ) scores are associated with objective measures of visual function in early and intermediate age-related macular degeneration (AMD). Cross-sectional study of subjects with early AMD Age-Related Eye Disease Study (AREDS) stage 2, N = 33), intermediate AMD (AREDS stage 3, N = 47), and age-matched healthy controls (N = 21). Subjects were interviewed with the LLQ. Psychophysical tests performed included best-corrected visual acuity (BCVA), mesopic microperimetry, dark adaptometry (DA), low luminance visual acuity (LLVA), and cone contrast test (CCT). Low luminance deficit (LLD) was the difference in the number of letters read under photopic versus low luminance settings. The relationship between LLQ and visual function test scores was assessed with linear regression. Subjects with intermediate AMD had significantly lower LLQ composite scores (mean = 75.8 ± 16.7; median = 76, range [29, 97]) compared with early AMD (mean = 85.3 ± 13.3; median = 88, range [50, 100], P = 0.007) or controls (mean = 91.4 ± 6.5; median = 94, range [79, 99], P < 0.001) in the overall cohort. LLQ composite scores were associated with computerized BCVA (β = 0.516), computerized LLVA at two background luminance (1.3 cd/m2, β = 0.660; 0.5 cd/m2, β = 0.489) along with their respective computerized LLDs (β = -0.531 and -0.467), rod intercept (β = -0.312), and CCT green (β = 0.183) (all P < 0.05). Only the computerized LLVAs and computerized LLDs remained statistically significant after adjusting for AMD versus control status (P < 0.05). Among AMD subjects, LLQ composite scores were significantly associated with the computerized LLVAs (β = 0.622 and 0.441) and LLDs (β = -0.795 and -0.477) at both the 1.3 and 0.5 cd/m2 luminance levels, respectively, and these associations remained significant after adjusting for AMD severity (P < 0.05). Among subjects with early and intermediate AMD, LLQ scores were significantly associated with computerized LLVA and LLD. LLQ is a useful patient-centered functional measure of visual impairment in early and intermediate AMD.